Volatilitas Harga Jagung dan Integrasi Pasar di Indonesia - Fadhilah, Muhammad Luthfie; Putri, Levana Masitajasmin; Fauziah, Irma; Cahyaningtyas, Nur Indah; Rahmaningtyas, Avivah; Novitaningrum, Restie; Simamora, Liska (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Maize is the main raw material for animal feed, and weakening maize prices have a significant impact on the prices of livestock products such as chicken and eggs. The high demand for animal feed can drive up maize prices. Keywords: Volatility, Integration, Market, Maize Price. This condition is further exacerbated during the COVID-19 pandemic, disruptions to the global supply chain, distribution regulations, and economic instability have caused maize price volatility to increase sharply. The purpose of this study is to analyze maize price volatility and market integration at the producer, consumer and world levels. This study uses secondary data obtained from the Central Statistics Agency (BPS), Ministry of Trade, Ministry of Agriculture, Food Prices and the World Bank. The data analysis used is the coefficient of variation and Vector Error Correction Model (VECM). The results show that maize price volatility at the producer and consumer levels is relatively low, while at the world level it is high. The results of the integration analysis obtained prices at the producer, consumer, and world levels have long-term integration. Only consumer maize prices (HJK) significantly adjust in the short term to long-term sufficiency. Maize prices at the consumer level are greatly influenced by producer prices, which indicates that vertical price transmission from producers to consumers is quite strong. The influence of world prices exists, but is relatively small and indirect. Production costs, input availability, and market channels are the main factors in determining maize prices at the producer level. Efficient marketing channels can result in better price realization for farmers so that farmers get better profits. The government must be able to maintain a good farming climate for farmers